Hubungan Pengetahuan Ibu Baduta dengan Pemberian Imunisasi Dasar - Franzisca, Vani -; Rahmi, Sania Lailatu; Sefrina, Yosi (Jurnal Bidan Mandiri, 2025)
Basic immunization is an important effort in preventing infectious diseases in children and boosting immunity from an early age. However, basic immunization coverage in Indonesia is still uneven. In West Sumatra Province, only Pesisir Selatan District has achieved the national target of 90%, while Bukittinggi City has only reached 70.7% in 2024. In the service area of the Guguk Panjang Community Health Center, immunization coverage is only 68.1%, including the Padang Gamuak Health Post, which also has not met the target. Maternal knowledge is a major factor influencing immunization completeness, as mothers with good knowledge tend to be more compliant with the immunization schedule. This study aims to determine the relationship between maternal knowledge and basic immunization completeness at the Padang Gamuak Health Post, Guguk Panjang Community Health Center. This study is a quantitative analytical study with a cross-sectional design conducted from January to June 2025. The study population consisted of 94 mothers of infants, and a sample of 48 people was selected using simple random sampling. Data were collected through knowledge questionnaires and KIA books, then analyzed using the Chi-Square test. The results showed that 52.08% of respondents had good knowledge, and 56.25% of children had received complete basic immunization. There was a significant relationship between mothers' knowledge and the completeness of basic immunization (p = 0.000). It was concluded that good maternal knowledge can increase the coverage of complete basic immunization. Therefore, community health centers are expected to continue to improve education and counseling on the importance of immunization.